Application of track detectors to measure neutrons emitted from a 14 MeV neutron generator. (December 2018) - Malinowska, A.; Szydłowski, A.; Kwiatkowski, R.; Burakowski, S.; Gierlik, M.; Malinowski, K.; Rzadkiewicz, J.
Abstract: This paper reports on applicability of a polyallyl-diglycol-carbonate (PADC) detectors of the CR-39 TASTRAK type as integrated neutron ﬂuence sensors for monitoring of neutrons emitted from 14 MeV neutron generator. Neutron generators such as SODERN Model: GENIE 16 D are powerful emitters of fusion neutrons from DT reactions with yields up to 2 × 10 8 n·s −1 . The presented generator is now available worldwide as a source of neutrons with a rather wide range of applications in medicine, industry and in the detection of hazardous materials. Before using in those measurements, the CR-39 TASTRAK type detector was precisely calibrated. Rectangular track detector samples prepared for neutron ﬂux measurements are in the form of "sandwiches" consisting of a detector plate covered by a thick polythene (PE) radiator and in some part by a Cu-filter. In order to estimate how many neutrons could be converted into recoil-protons we have performed computer calculations by means of MC methods. Highlights: To use CR-39 detectors carefully calibration measurements were carried out. The computer simulations were conducted in order to estimate conversion factor. The activation technique were also used for verification of obtained results.